Composição e distribuição espaço-temporal dos Crustacea componentes da megafauna bêntica na plataforma continental de Sergipe - Mendonça, Luana Marina de Castro (2016)
Crustacea is mentioned as a dominant group in almost all continental shelf environments around the Brazilian coast and the taxonomic group with more studies. However, the carcinofauna of some Brazilian shelfs are poorly known, such as Sergipe state. The aim of this study is contribute for the knowledge of Crustacea, components of benthic megafauna from continental shelf of Sergipe and understand how populations communities vary spatially and temporally. The crustaceans were collected with otter trawl in two different seasonal periods, 18 stations between 36°32'W 10°36'S e 37°05’W 11°21’S distributed in 6 transects and in 10, 20 and 30 m isobaths, for a total of 72 stations sampled, between the years 1999 and 2000. Environmental parameters from water and sediment were collect in each station. In laboratory, the organisms were identified to species level and analyzed in terms of richness, abundance and biomass, and the community in terms of diversity indices, equitativity, frequency of occurrence and relative importance indices. The Crustacea was represented by 62749 individuals, distributed in 71 taxa, 199.97 kg of biomass and 77.81km² of density. The collected organisms are representatives of 2 orders, 4 infraorders, 25 families, 46 genus and 64 species. Brachyura presented the greatest number of taxa with 39, followed by Caridea with 12, Dendrobranchiata with 9, Anomura with 7, Stomatopoda with 2 and Achelata with 1. The community was abundant and displayed considerable richness; however, diversity and equitability were low, showing the dominance of the species X. kroyeri, N. schmitti, L. schmitti, F. schmitti and C. ornatus. The fauna varied in space and time and the main abiotic parameters that explain these variations were depth, temperature and the bottom type, especially coarser sediments with high levels of sand and gravel. Six species of Crustacea were recorded for the first time from Sergipe continental shelf, 3 Brachyura (Allactaea lithostrota, Coryrhynchus riisei e Ericerodes minusculus), 2 Caridea (Alpheus armillatus, A. cf. packardii e A. intrisecus) e 1 Stomatopoda (Squilla brasiliensis).